The Impact of Child Exploitation on Children's Mental and Emotional Health in Surakarta According to Law No. 35 Article 76 I of 2014 on Child Protection. 35 Article 76 I of 2014 on Child Protection - Nabilla Dea Azzahramajid; Diana Setiawati (Universitas Muhammadiyah Surakarta, 2025)
In accordance with Law No. 35 Article 76 I of 2014 on child protection, this study investigates the impact of child exploitation on the mental and emotional health of children in Surakarta. This study shows that child exploitation adversely affects children's mental and emotional health. That many of them experience anxiety, depression, sleep disorders, and also experience high psychological burden, which causes emotional disorders such as anger, frustration, and deep sadness. In addition, this study found that Law No. 35 Article 76 I of 2014 provides significant protection for child victims of exploitation in Surakarta. The law also regulates the sanctions given to the perpetrators of child exploitation. This study aims to review and analyze how much child exploitation in Surakarta and what are the factors that cause child exploitation that affect the mental and emotional health of children. Data analysis is conducted using empirical methods to explore cases of experience and concrete facts by means of observation and interviews. The results of this study suggest that communities and government agencies should be more aware of combating child exploitation. To prevent children from exploitation that harms their mental and emotional health, strict education and socialization should be conducted.